Crosstalk between proximal tubular epithelial cells and other interstitial cells in tubulointerstitial fibrosis after renal injury - Guo, Congcong; Cui, Yuying; Jiao, Mingwen; Yao, Jinming; Zhao, Junyu; Tian, Yutian; Dong, Jianjun; Liao, Lin (Frontiers in Endocrinology, 2024)
The energy needs of tubular epithelial components, especially proximal tubular epithelial cells (PTECs), are high and they heavily depend on aerobic metabolism. As a result, they are particularly vulnerable to various injuries caused by factors such as ischemia, proteinuria, toxins, and elevated glucose levels. Initial metabolic and phenotypic changes in PTECs after injury are likely an attempt at survival and repair. Nevertheless, in cases of recurrent or prolonged injury, PTECs have the potential to undergo a transition to a secretory state, leading to the generation and discharge of diverse bioactive substances, including transforming growth factor-β, Wnt ligands, hepatocyte growth factor, interleukin (IL)-1β, lactic acid, exosomes, and extracellular vesicles. By promoting fibroblast activation, macrophage recruitment, and endothelial cell loss, these bioactive compounds 2 This is a provisional file, not the final typeset article stimulate communication between epithelial cells and other interstitial cells, ultimately worsening renal damage. This review provides a summary of the latest findings on bioactive compounds that facilitate the communication between these cellular categories, ultimately leading to the advancement of tubulointerstitial fibrosis (TIF).